2018
DOI: 10.1084/jem.20170308
|View full text |Cite
|
Sign up to set email alerts
|

The human CIB1–EVER1–EVER2 complex governs keratinocyte-intrinsic immunity to β-papillomaviruses

Abstract: Patients with epidermodysplasia verruciformis (EV) and biallelic null mutations of (encoding EVER1) or (EVER2) are selectively prone to disseminated skin lesions due to keratinocyte-tropic human β-papillomaviruses (β-HPVs), which lack E5 and E8. We describe EV patients homozygous for null mutations of the gene encoding calcium- and integrin-binding protein-1 (CIB1). CIB1 is strongly expressed in the skin and cultured keratinocytes of controls but not in those of patients. CIB1 forms a complex with EVER1 and EV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 103 publications
2
95
0
Order By: Relevance
“…PLINK software (http://zzz.bwh.harvard.edu/plink/) was used to further filter SNPs with population-based filters according to the ethnicity of the kindred. A subset of 163,807 autosomal SNP markers common to the 2 genotyping arrays and optimized to decrease their linkage disequilibrium (LD) was used for linkage analysis, as previously described (88). Parametric multipoint linkage analyses were performed with MERLIN (http://csg.sph.umich.…”
Section: Discussionmentioning
confidence: 99%
“…PLINK software (http://zzz.bwh.harvard.edu/plink/) was used to further filter SNPs with population-based filters according to the ethnicity of the kindred. A subset of 163,807 autosomal SNP markers common to the 2 genotyping arrays and optimized to decrease their linkage disequilibrium (LD) was used for linkage analysis, as previously described (88). Parametric multipoint linkage analyses were performed with MERLIN (http://csg.sph.umich.…”
Section: Discussionmentioning
confidence: 99%
“…HPV‐24 is among the HPV species associated with epidermodysplasia verruciformis (EV), a genetic or acquired skin disease characterized by multiple pre‐malignant verrucous papules and macules caused by chronic HPV infection . Genetic EV typically results from loss of function mutations in EVER1, EVER2, or CIB1, while acquired EV may result from iatrogenic immunosuppression in organ transplant patients, HIV infection, or other medical conditions leading to compromised immune function. In fact, ruptured epidermoid cysts infected with HPV‐24, as well as EV‐associated HPV‐20 and HPV‐80, have been reported in one patient with idiopathic CD4 lymphopenia and chronic Mycobacterium avium intracellulare infection .…”
Section: Discussionmentioning
confidence: 99%
“…HPV-24 is among the HPV species associated with epidermodysplasia verruciformis (EV), a genetic or acquired skin disease characterized by multiple premalignant verrucous papules and macules caused by chronic HPV infection. 19 Genetic EV typically results from loss of function mutations in EVER1, EVER2, or CIB1, 20,21 Mycobacterium avium intracellulare infection. 22 In contrast, β HPV species typically produce asymptomatic infection in immunocompetent reported for bacteria and fungi.…”
Section: Discussionmentioning
confidence: 99%
“…EVER1 and EVER2 are able to repress zinc-dependent transcription. However, in a different study, endogenous deficiencies of neither protein were found to be associated with overt disturbed zinc homeostasis [57].…”
Section: Cell-autonomous and Extrinsic Immune Control Of Beta-human Pmentioning
confidence: 94%